Development of novel lutein nanocrystal formulation with improved oral bioavailability and ocular distribution. (October 2019) - Seto, Yoshiki; Ueno, Kodai; Suzuki, Hiroki; Sato, Hideyuki; Onoue, Satomi
Graphical abstract: Highlights: A nanocrystal formulation of lutein (NC/LT) was prepared using a bottom-up system. The dissolution behavior of NC/LT was higher than that of crystalline LT in water. Orally-taken NC/LT showed higher oral absorption of LT compared with crystalline LT. NC/LT may be an efficacious dosage form to enhance nutraceutical properties of LT. Abstract: A nanocrystal formulation of lutein (NC/LT) was prepared by particle size reduction approach with a bottom-up system to improve nutraceutical properties of LT, and physicochemical and pharmacokinetic characterizations of NC/LT were undertaken. In NC/LT, LT nanoparticles with a mean diameter of 230 nm existed in a crystalline state, and, in comparison with crystalline LT, NC/LT exhibited a marked improvement in dissolution/dispersion behavior of LT in water. Orally-administered NC/LT exhibited enhanced oral absorption of LT in male Sprague-Dawley rats, as evidenced by relative bioavailability of 15.2 to crystalline LT. After oral administration of LT samples (100 mg-LT/kg, 7 days) to male Sprague-Dawley rats, the ocular accumulation of LT in NC/LT was 3.4-fold higher than that in crystalline LT. Upon these findings, particle size reduction of LT would be efficacious to improve its dissolution and pharmacokinetic characteristics, and NC/LT may be an attractive dosage form to enhance the nutraceutical properties of LT.